Information, communication and computing technology : 4th International Conference, ICICCT 2019, New Delhi, India, May 11, 2019, Revised selected papers /: 4th International Conference, ICICCT 2019, New Delhi, India, May 11, 2019, Revised selected papers. (2019) - Unknown
No abstract available